2021
DOI: 10.3390/ijerph18126583
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors of Early Adolescence in the Criminal Career of Polish Offenders in the Light of Life Course Theory

Abstract: Life course theory (LCT) diagnoses childhood and adolescent factors that determine an individual’s involvement in crime in the future. Farrington lists eight key correlates identified by empirical analyses of criminal careers. In this paper, we seek to discuss the inconsistencies with LCT that we observed in our three empirical studies of the criminal careers of Polish offenders. During 12 years of qualitative research, we conducted direct observations and in-depth interviews in juvenile correction institution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Women influenced by the justice system have disproportionate rates of adverse childhood experiences and trauma in the form of abuse, violence, and separation of families starting at an early age (Pekala et al., 2021). All participants in our study described extreme abuse, neglect, and/or violence that led them to leave home at an early age, become homeless as teenagers, and rely on older sexual partners to survive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Women influenced by the justice system have disproportionate rates of adverse childhood experiences and trauma in the form of abuse, violence, and separation of families starting at an early age (Pekala et al., 2021). All participants in our study described extreme abuse, neglect, and/or violence that led them to leave home at an early age, become homeless as teenagers, and rely on older sexual partners to survive.…”
Section: Discussionmentioning
confidence: 99%
“…This poverty and the need for survival contributed to sex work for most of the participants in our study, which is prevalent among populations that experience felony disenfranchisement (Karlsson & Zielinski, 2020). Substance use as a means of coping is prevalent throughout the life course of women who experience arrest and is often the result of prior trauma (Cleveland et al., 2020; Karlsson & Zielinski, 2020; Pękala et al., 2021). The participants in our study also described traumatic experiences that contributed to their substance use disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Because we carried out these interviews in correctional facilities, authorities did not permit us to use recording equipment. Following others, we employed an open-ended biographical-focused questionnaire that was subject-driven (Chomczyński 2018;Fleetwood 2015;Noaks and Wincup 2004;Pękala et al 2021aPękala et al , 2021bSilverman 2011). Some interviews were prearranged while others occurred by a chance meeting and discussion with a dealer that we encountered in our fieldwork.…”
Section: Research Setting and Methodsmentioning
confidence: 99%
“…Ricardo, a dealer, received training from peers and older adults. In informal discussions, lowprofile dealers revealed that their entry began by observing those more experienced at the trade through learning and imitation (Akers et al 1979;Pękala et al 2021aPękala et al , 2021bTarde 1962). The main difference in our findings and those cited above is our subjects' unwillingness to acknowledge their activity as deviant (Becker 1963).…”
Section: Entering the Trade Of Cannabis Dealingmentioning
confidence: 99%